Identifikasi Bahaya, Penilaian Risiko, dan Pengendalian Risiko Kecelakaan Kerja di PT AW Plus UPVC Bali - Dustin Fandy; Kriswanto Widiawan (Jurnal Titra, 2022)
PT AW PLUS UPVC Bali is a company engaged in the production of UPVC-based doors and windows located on the island of Bali. The production process of PT AW PLUS UPVC Bali involves tools, cutting machines, and welding machines, thus if the production process is not carried out carefully, injuries can occur. This company also does not have a work hazard identification document, thus the company is still unable to fully understand the risks of accidents that can arise in each of its production processes. Therefore, the purpose of this final project is to design hazard identification, risk assessment, and risk control or HIRARC to reduce the risk of injury in the production process of PT AW PLUS UPVC Bali. The writing of this final project starts with direct observation and interviews with the company. After the risk has been identified, a risk assessment will then be carried out by determining the level of likelihood and severity of the risk. The results of the assessment show 43 potential hazards with medium risk rating, and 3 potential hazards with extreme risk rating.